Legal Protection of Forest Customary Rights in Land Procurement from the Mineral Mining Industry - Istijab, Istijab; Safa’at, Rachmad; Permadi, Iwan; Koeswahyono, Imam (Faculty of Law, Universitas Brawijaya, 2022)
This research aims to determine if legal protection is available for the use of forests, which are the customary rights of Adat and Indigenous Community from the mineral mining sector, which demands the use of extremely large territories. Fulfillment the utilizes state-controlled forest land, including protected forests, and industrial forests could be challenges. By considering environmental sustainability, legal protection ensures sustainable growth. To legally maintain customary forest rights, this study employs normative-juridical research utilizing primary and secondary legal sources about the acquisition of land for the mining sector, particularly for mineral mining. Agrarian, forestry, mining, and environmental protection and preservation legislation and decisions of the Constitutional Court of Indonesia on mining are examples of authoritative primary legal texts. All legal publications—including books, dictionaries, journals, and comments on court judgments—are considered secondary legal sources. This study finds that the legal protection of Adat and Indigenous Community’s customary forest rights over the availability of land for mining firms must be profitable, prosperous, and fair for Adat and Indigenous Community members. Adat and Indigenous Community are community associations that live and grow happily together in a hereditary region based on ancestry and similarity of habitation. Forest use for this purpose requires a Borrowing and Use Permit, which must include criteria for periodic, quantitative, and transparent environmental management, and preservation.